The survival of unique corporate cultures - Gil S. Epstein; Renana Lindner Pomerantz (Bar-Ilan University, Department of Economics, 2016)
In this paper we identify two situations that can lead a firm to hire an executive who supports a corporate culture that differs from the firm's current culture. In the first case, there is similarity between the firm's culture and that of the candidate and in the second case, executives who support the firm's culture constitute a minority of available candidates. In both cases the firm prefers to hire an available candidate, rather than risk a prolonged vacancy. We show how these scenarios can lead to the eradication of unique cultures and to the perpetuation of more common cultures.
Keywords: 330; Corporate Culture; Organizations; Minority